CLASSROOM MANAGEMENT: THE TOOL FOR MOTIVATION OF YOUNGER LEARNERS - Kasyanova, D.V.; Kudritskaya, M.I. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2017)
In this article, the concepts of classroom management and motivation of learning activity, as well as their interrelation and role in the educational process are considered. In the center of attention is the classification classroom management activities aimed at increasing the level of learners' motivation of primary school in the lessons of English language. A detailed description of each type of activities from this classification is also considered and there are the description of approbation of the classification conducted in the period of pre-diploma practice and the evidence of its effectiveness.
Keywords: classroom management; motivation; classification of activities; younger learners; approbation; English lesson